Enforcement of the Police Professional Code of Ethics Analysis of the Case Study of Inspector General Ferdy Sambo's Criminal Acts - Widodo, Widodo; Basrawi, Basrawi; Satmawati, Satmawati; Ananda, Firna Dwi; Paradina, Nur Afikah; Rasti J, Ardina (Sangia Nibandera Law Research, 2025)
This research aims to find and analyze violations of the code of ethics for the National Police public relations profession (case study Ferdi Sambo). The method used in this research is a qualitative descriptive method with data collection carried out by researchers through library research (library study). The data analysis technique uses a data analysis approach, namely data collection, data reduction, data display, conclusion drawing. The results of this research show that the violation of the professional code of ethics in the Ferdi Sambo case study has tarnished the good name of the National Police institution, damaged the image and reputation of the National Police. National Police Public Relations is able to resolve problems quickly by increasing the role of National Police Public Relations to expert prieciber, problem solving communication facilitator, technician communication facilitator. Analysis of this case provides a lesson for the public that when carrying out a profession one must be professional and not involve emotional feelings whose impact is not only detrimental to oneself but also detrimental to the institution and the public.